Genome-Wide Analysis of Cell-Free DNA Methylation Profiling for the Early Diagnosis of Pancreatic Cancer - Li, Shengyue; Wang, Lei; Zhao, Qiang; Wang, Zhihao; Lu, Shuxian; Kang, Yani; Jin, Gang; Tian, Jing (Frontiers in Genetics, 2020)
As one of the most malicious cancers, pancreatic cancer is difficult to be treated due to the lack of effective early diagnosis. Therefore, it is urgent to find reliable diagnostic and predictive markers for early detection of pancreatic cancer. In recent years, the detection of circulating cell-free DNA (cfDNA) methylation in plasma has attracted global attention for noninvasive and early cancer diagnosis. Here, we carried out a genome-wide cfDNA methylation profiling study of pancreatic ductal adenocarcinoma (PDAC) patients by Methylated DNA Immunoprecipitation coupled with high-throughput sequencing (MeDIP-seq). Compared with healthy individuals, 775 differentially methylated regions (DMRs) located in promoter regions were identified in PDAC patients with 761 hypermethylated and 14 hypomethylated regions; meanwhile, 761 DMRs in CpG islands (CGIs) were identified in PDAC patients with 734 hypermethylated and 27 hypomethylated regions (p-value < 0.0001). 143 hypermethylated DMRs were further selected which were located in promoter regions and completely overlapped with CGIs. After performing the least absolute shrinkage and selection operator (LASSO) method, a total of 8 probes from 8 genes were found to fairly distinguish PDAC patients from the healthy individuals, including TRIM73, FAM150A, EPB41L3, SIX3, MIR663, MAPT, LOC100128977 and LOC100130148. In conclusion, this work identified a set of 8 differentially methylated markers that may be potentially applied in noninvasive diagnosis of pancreatic cancer.